2014
DOI: 10.1016/j.ridd.2014.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Memory failures for everyday tasks in caregivers of children with autism

Abstract: The stress of caring for a loved one with chronic illness has been linked with impairments in cognitive processes such as attention and problem solving, though few studies have examined the impact on memory. Compromised cognition, in particular, aspects of everyday functioning such as remembering medical instructions and appointments, might affect caregivers' ability to maintain the consistency and quality of care needed by the child. A sample of 31 caregivers of children with autism and 51 parents of neuro-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…As far as we are aware, at the time of conception of this study no other study had assessed memory differences between parents of CSHCNs and TD children. However, a study published very recently reported worse prospective and retrospective memory in caregivers of children with autism compared to control parents, and these memory deficits were related to stress levels (Lovell et al ., ). As with the sleep findings, in the current study there may have been a ceiling effect, as memory scores of both groups of parents had means that were multiple points above validated norms on both prospective and retrospective memory scales, suggesting clinically significant poor memory in general among the parents in our sample (Crawford et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As far as we are aware, at the time of conception of this study no other study had assessed memory differences between parents of CSHCNs and TD children. However, a study published very recently reported worse prospective and retrospective memory in caregivers of children with autism compared to control parents, and these memory deficits were related to stress levels (Lovell et al ., ). As with the sleep findings, in the current study there may have been a ceiling effect, as memory scores of both groups of parents had means that were multiple points above validated norms on both prospective and retrospective memory scales, suggesting clinically significant poor memory in general among the parents in our sample (Crawford et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The current study's parents of CSHCNs were similar to Lovell et al . 's () sample of parents of children with autism on both prospective (Lovell et al ., mean: 27.2; current study, mean: 26.1) and retrospective (Lovell et al ., mean: 21.6; current study, mean: 19.8) memory, but the control parents in their sample scored better on prospective (Lovell et al ., mean: 20.0; current study, mean: 24.7) and retrospective (Lovell et al ., mean: 16.8; current study, mean: 19.6) memory than the controls in our sample. Despite the fact that the control parents in the current study reported poorer memory compared to the controls in Lovell et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lovell, Elliot, Liu, and Wetherell (2014) reported that family caregivers of individuals with autism reported more problems in both their prospective and retrospective memory than their counterparts with a typically developing child. Similarly, Song, Mailick, Greenberg, and Ryff (2016) found that older mothers of a son or daughter with developmental disabilities had worse episodic memory than younger mothers, and that those who experienced high levels of negative parenting experiences showed the worst cognitive functioning.…”
Section: Executive Functioning Limitations As a Mediatormentioning
confidence: 99%
“…Psychological distress have also been investigated among caregivers particularly of people with chronic obstructive pulmonary disease [90], patients with psychosis [91][92], patients with schizophrenia [93], cancer patients [94], symptomatic lung cancer patients [95], women with ovarian cancer [96], patients with lung cancer [97][98], and individuals with affective disorders [99]. Studies on psychological distress have also been done on caregivers of children with autism spectrum disorder [100][101][102][103] and children with asthma [104], children with a disorder of sex development [105][106]. However, not much has been done on caregivers of normal preschool pupils in Nigeria generally and in Ekiti State to be specific.…”
Section: Statement Of the Problemmentioning
confidence: 99%